Bifunctional catalyst Pd–Al-MCM-41 for efficient dimerization–hydrogenation of β-pinene in one pot. Issue 75 (10th October 2017) - Zhang, Song; Xu, Chao; Zhai, Guoqing; Zhao, Mingliang; Xian, Mo; Jia, Yuxiang; Yu, Zongjiang; Liu, Fusheng; Jian, Fangfang; Sun, Weizhi
Abstract : A new type of bimetallic palladium and aluminum incorporated mobile crystalline materials (Pd–Al-MCM-41) as bifunctional catalysts has been hydrothermally synthesized. Abstract : A new type of bimetallic palladium and aluminum incorporated mobile crystalline materials (Pd–Al-MCM-41) as bifunctional catalysts has been hydrothermally synthesized. Characterization shows that these molecular materials exhibit an ordered mesoporous structure, high surface area and a good dispersion of palladium in the frame. The catalytic activity of the Pd–Al-MCM-41 for the dimerization–hydrogenation reaction system of β-pinene in one pot has been systematically studied. Pd0.5 –Al30 -MCM-41 (SiO2 /Al2 O3 = 30, 0.5 wt% palladium content) was found to be the best catalyst which gave a dimer yield of up to 64.7%. It is worth noting that palladium shows a good synergic catalytic effect with aluminum in the dimerization reaction and enhances the dimerization yield. Furthermore, the bifunctional catalyst displayed a good activity over 4 runs.